2013
DOI: 10.1097/gme.0b013e3182a14372
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive history and postmenopausal rheumatoid arthritis among women 60 years or older

Abstract: Women who experience menopause before 40 years of age seem to be at increased risk for postmenopausal rheumatoid arthritis. Conversely, age at menarche and pregnancy history may not predict rheumatoid arthritis after menopause. Further research is needed to confirm and elucidate these epidemiological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…Another study found that 25% of women with RA reported age at menopause as <45 years . Other studies have found that early menopause is associated with increased risk for RA . Based on this literature, it appears that a higher percentage of postmenopausal women with RA have had early menopause; however, we were unable to confirm this, as there is no control group in our study design.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Another study found that 25% of women with RA reported age at menopause as <45 years . Other studies have found that early menopause is associated with increased risk for RA . Based on this literature, it appears that a higher percentage of postmenopausal women with RA have had early menopause; however, we were unable to confirm this, as there is no control group in our study design.…”
Section: Discussionmentioning
confidence: 63%
“…Several studies looking at age at menopause and RA have supported that it may play a role in risk for RA as well as disease activity in established RA. Women with older age at menopause have been shown to have reduced risk of developing RA compared to those who had early age at menopause , while early age at menopause has been associated with increased risk of developing RA . In addition, one study found that patients who had early menopause were less likely to be rheumatoid factor (RF) positive or need biologic agent therapy than those with normal age at menopause .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the flowchart of literature inclusion and exclusion. We identified 47 publications for full-text evaluation, of which 30 publications were further excluded because they did not fulfill the inclusion criteria (ie, conference abstracts,3442 meta-analyses/reviews,5058 letters to editor/comments,59 cross-sectional studies,29,30 providing insufficient data,28 involving the same study population or overlapped data,8,31–33 involving family cases,13,17 reporting the relationship between noncontraceptive hormones and RA among perimenopausal and postmenopausal women,11 and using OCs users with less than one patient as reference9). Therefore, our meta-analysis was based on 17 publications, including 12 case-control and five cohort studies published between 1982 and 2010 4,7,10,12,1416,1827.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, there are consistent data supporting that estrogens have a protective effect in the clinical development of the disease. These include that early menopause is associated with the subsequent development of RA, most of the patients experience partial or complete remission during pregnancy but relapse during the postpartum period, and there is a reduction in the incidence of disease onset during pregnancy but the incidence increases in the postpartum [57,[59][60][61][62][63][64][65][66][67]. Interestingly, estrogens have both pro-and anti-inflammatory effects that may explain their paradox in RA pathogenesis.…”
Section: Hormonal Factorsmentioning
confidence: 99%